Dog-assisted interventions for adults diagnosed with schizophrenia and related disorders: a systematic review - Tyssedal, Malene Kalsnes; Johnsen, Erik; Brønstad, Aurora; Skrede, Silje (Frontiers in Psychiatry, 2023)
Background Many individuals diagnosed with schizophrenia and related disorders experience insufficient symptom relief from currently available treatment options. Researching additional venues should be prioritized. This systematic review, designed in accordance with PRISMA, examined the effect of targeted and structured dog-assisted interventions as a supplementary treatment. Methods Randomized as well as non-randomized studies were included. Systematic searches were conducted in APA PsycInfo, AMED, CENTRAL, Cinahl, Embase, Medline, Web of Science, and in several sources covering “gray” (unpublished) literature. In addition, forward and backward citation searches were performed. A narrative synthesis was conducted. Quality of evidence and risk of bias were assessed in accordance with GRADE and RoB2/ROBINS-I criteria. Results 12 publications from 11 different studies met eligibility criteria. Overall, studies showed diverging results. General psychopathology, positive and negative symptoms of psychosis, anxiety, stress, self-esteem, self-determination, lower body strength, social function, and quality of life were among the outcome measures with significant improvement. Most documentation for significant improvement was found for positive symptoms. One study indicated significant deterioration of non-personal social behavior. The risk of bias was high or serious for most of the outcome measures. Three outcome measures were associated with some concerns regarding risk of bias, and three with low risk of bias. Quality of evidence was graded low or very low for all outcome measures. Conclusions The included studies indicate potential effects of dog-assisted interventions for adults diagnosed with schizophrenia and related disorders, mostly beneficial. Nevertheless, low number of participants, heterogeneity, and risk of bias complicate the interpretation of results. Carefully designed randomized controlled trials are needed to determine causality between interventions and treatment effects.